Coherent spin dynamics in a helical arrangement of molecular dipoles - Diaz, Elena; Gutierrez, Rafael; Gaul, Christopher; Cuniberti, Gianaurelio (Giovanni); Dominguez-Adame, Francisco (AIMS Materials Science, 2017)
Experiments on electron transport through helical molecules have demonstrated the appearance of high spin selectivity, in spite of the rather weak spin-orbit coupling in organic compounds. Theoretical models usually rely on different mechanisms to explain these experiments, such as large spin-orbit coupling, quantum dephasing, the role of metallic contacts, or the interplay between a helicity-induced spin-orbit coupling and a strong dipole electric field. In this work we consider the coherent electron dynamics in the electric field created by the helical arrangement of dipoles of the molecule backbone, giving rise to an effective spin-orbit coupling. We calculate the spin projection onto the helical axis as a figure of merit for the assessment of the spin dynamics in a very long helical molecule. We prove that the spin projection reaches a steady state regime after a short transient. We compare its asymptotic value for different initial conditions, aiming to better understand the origin of the spin selectivity found in experiments.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Helical molecules; Nanoscale materials; Spin polarized transport; Spin sensitivity; Spin-orbit coupling